P218 The needs of long COVID service users in hampshire and isle of wight ICS: a prospective mixed methods evaluation. (11th November 2022) - Barker, RE; Sibley, A; Wheeler, R; Russell, R
Abstract : Introduction and Objectives: To better understand the support needs of patients with Long Covid an evaluation of the Long Covid service in the Hampshire and Isle of Wight Integrated Care System (ICS) was undertaken to inform service improvement. Methods: This prospective mixed methods evaluation conducted between September and October 2021 included an ICS-wide online survey, as well as interviews and focus groups with Long COVID service users. Results: Of 1005 service users approached, 139 (14%) completed the survey. Three focus groups (which included 11 participants) and 17 interviews were conducted. A fifth of service users who responded to the survey either did not feel empowered to identify support or felt that support was not detectable or available. Just over half of service users were reliant on family and friends for support (52%) and a reasonable proportion sought private healthcare support (13%). A wide range of needs and issues were identified from the survey, interviews and focus groups, with fatigue and breathlessness the most commonly reported symptoms. The varied types of support reported are detailed in table 1 . There was a particular desire for peer-led and professional-led support groups, to share concerns, ideas, and learning – particularly as clinical evidence of the condition is continually evolving. Four areas were highlighted for consideration when designing Long COVID services: 1) optimising information sharing between referral and assessment, to make the most of any delays due to capacity pressures; 2) offering an accessible model of care, taking a hybrid face-to-face and virtual approach and periodic 'check-ins' for patients affected over the long term; 3) undertaking comprehensive, holistic assessments which lead to individually tailored management plans; 4) being aware of deprivation and other factors (such as digital literacy) which could influence decision-making to better offer individualised management. A model of care for delivering Long COVID support services was recommended to the ICS based upon these findings. Conclusions: These findings corroborated recently published NICE recommendations for managing Long COVID and therefore provide further justification for rapid uptake of the NICE recommendations. These findings may also offer an adaptable model to effectively operationalise NICE recommendations going forward.